Dietary Inflammatory Index and Cognitive Function: Findings from a Cross-Sectional Study in Obese Chinese Township Population from 45 to 75 Years - Huang H; Li J; Shen J; Zhao T; Xiao R; Ma W (Dove Medical Press, 2024)
Hongying Huang, Jinchen Li, Jingyi Shen, Tong Zhao, Rong Xiao, Weiwei Ma School of Public Health, Beijing Key Laboratory of Environmental Toxicology, Capital Medical University, Beijing, 100069, People's Republic of ChinaCorrespondence: Weiwei Ma, School of Public Health, Beijing Key Laboratory of Environmental Toxicology, Capital Medical University, Beijing, 100069, People's Republic of China, Tel/Fax +86-10-83911651, Email weiweima@ccmu.edu.cnBackground and Objective: Cognitive dysfunction is highly prevalent in obese people, and food is a key factor in obesity, and dietary inflammatory index (DII) can reflect whether diet has anti-inflammatory or pro-inflammatory potential. In addition, dietary fatty acid consumption is linked to inflammation, obesity, and cognitive impairment. Erythrocyte membrane fatty acids can reflect dietary fatty acid intake. Our hypothesis was that erythrocyte membrane fatty acids might have a significant impact on the relationship between DII and cognition in obese individuals, and we designed experiments to test the hypothesis.Methods: In three villages in Beijing, we collected 579 respondents from individuals 45 to 75 years old and categorized them by body mass index. The Montreal Cognitive Assessment (MoCA) score and DII score was calculated and gas chromatography was used to measure the proportion of erythrocyte membrane fatty acids. The relationship between the DII score and cognition was examined using multiple linear regression and binary logistic regression. Mediation analysis can help to understand the causal chain between variables, deeply explore the internal relationship and mechanism of action between variables. So a multiple chain mediation model was developed to investigate the mediating factors between the DII score and cognitive association.Results: According to adjusted linear regression, higher DII scores were linked to lower MoCA scores in the obese group. The negative correlation between DII score and cognitive function score remains in binary linear regression. We discovered through mediation analysis that erythrocyte membrane fatty acids mediate the detrimental link between DII and cognitive function in obese individuals.Conclusion: We propose that higher DII scores in obese people are associated with a decline in cognitive function. In addition, this effect might be mediated via the fatty acids in the erythrocyte membrane.Keywords: mild cognitive impairment, dietary inflammatory index, obesity, fatty acids, chain mediation effect